PEMETAAN TINGKAT BAHAYA BENCANA LONGSOR DAN SISTIM PERENCANAAN TATA LETAK BANGUNAN DALAM TATA RUANG WILAYAH KOTA BAUBAU - Idham Handa; Taufik Taufik (Program Studi Teknik Lingkungan, Universitas Pembangunan Nasional Veteran Jawa Timur, 2020)
The study analyzes the level of landslide-prone and distribution and formulates the direction of the building layout information system to avoid landslide hazards. This research used quantitative descriptive design and survey design. The object of analysis is the slope of the slope, land use, type of soil, rainfall, geology, infrastructure, the presence of faults or faults, and gawir and settlement density. Data were analyzed by descriptive qualitative and spatial analysis (ArcView 3.2). Landslide hazard in Baubau City in the